2017
DOI: 10.1016/j.ejpsy.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis between the MMSE and the RUDAS for dementia screening in low educated people in a Spanish psychogeriatric clinic

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 21 publications
4
30
1
1
Order By: Relevance
“…Spain (Mateos-Alvarez et al, 2017). This was in line with the original RUDAS study in Australia (p= .04, Storey et al, 2004), but in contrast with other RUDAS studies in Australia which reported that age did not effect the RUDAS performance (Rowland et al, 2006;p= 0.5, Basic et al, 2009a;p= 0.65, Basic et al, 2009b;p= 0.42, Radford et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Spain (Mateos-Alvarez et al, 2017). This was in line with the original RUDAS study in Australia (p= .04, Storey et al, 2004), but in contrast with other RUDAS studies in Australia which reported that age did not effect the RUDAS performance (Rowland et al, 2006;p= 0.5, Basic et al, 2009a;p= 0.65, Basic et al, 2009b;p= 0.42, Radford et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…of older people with no formal education had very low scores within the 'visuo-constructional item' as compared to 30% with primary to secondary education, and 4% with university education, indicating the RUDAS more challenging, particularly on, when the participants were asked to draw the cube (Chaaya et al, 2015). However, in these studies outside Australia, respondents with low levels of education had higher scores in the RUDAS than the MMSE (Shaaban et al, 2013, Limpawattana et al, 2012a, and Mateos-Alvarez et al, 2017. There was also more variance from years of education on MMSE scores as compared to the RUDAS scores (44% versus 16%) within the Turkish respondents in Denmark; shorter years of education showed less educational bias for the RUDAS than the MMSE (Nielsen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations